Optimizing Food and Beverage Product Development: From the Past to the 21st Century and Beyond - Moskowitz, Howard; Roberts, Derek; Nagarajan, Divya; Gere, Attila (Edelweiss Applied Science and Technology, 2019)
Psychophysics is the oldest branch of experimental psychology, devoted to understanding the relation between physical stimuli (e.g., ingredients, processes) and subjective response. When applied to developing food products for commercial use, psychophysics takes on a new role, as a center point in an evolving ecology of many unrelated but relevant disciplines and professions. We present a short history of the application of psychophysics to the world of food product design, and the ecosystems which grew around it, evolved, changed, and had to be reengineered to be relevant for the 21st century.